(untitled) (Comparative & International Education Series, 2021)
Higher Education Institutions (HEIs) across the world have become increasingly international. Recently, increasing attention has been drawn towards graduate employability in Higher Education Institutions worldwide. The National Student Survey and Teaching Excellence Framework in the UK have brought graduate employability to the forefront of discussions. Much research has been devoted to enhancing undergraduate students’ employability skills and attributes through curriculum design and work-based learning; however, little attention has been paid to the employability of international students, particularly, doctoral students. This chapter aims to explore the perspectives of Chinese international doctoral students on their PhD experience and employability and to identify commonly used resources for career planning. Results show that students consider there is a significant difference between Chinese and Western employers when it comes to recruiting graduate students.